Teacher Beliefs and Emotion Expression in Light of Support for Student Psychological Needs: A Qualitative Study - Jiang JW; Vauras M; Volet S; Salo AE (MDPI, 2022)
This study explored teacher beliefs and emotion expression via six semi-structured interviews with teachers, and discussed the findings in relation to the Self-Determination Theory, which addresses teacher support for autonomy, competence, and relatedness. The findings showed that teacher beliefs about their roles as educators, carers, and providers of reassurance reflected expressing clear expectation, caring for students, and considering student perspectives and feelings; teacher beliefs about equality between teachers and students appeared connected with trust in students and encouragement of their self-initiation; teacher beliefs about closeness to students reflected caring for students; teacher expression of negative emotions by discussing the problem with students conveyed explanatory rationales for expected student behaviors. This study revealed that teacher beliefs about teacher-student power relations may be connected with teacher appraisals of student misbehaviors. The findings also suggest that teachers need to discuss the problem with students rather than lose their temper or suppress their emotion when they feel a need to direct-stage anger. Future research could investigate teachers' faking a particular emotion, such as faking indifference as revealed in the present study. Future research could also explore the reason for and harmfulness of embracing beliefs, e.g., negative expression of anger as a safety belt.